Search for the Depths of Education in the Treasury of B. Bitinas’ Pedagogical Thought - Aramavičiūtė, Vanda; Martišauskienė, Elvyda (Pedagogika, 2016)
Contemporary educational system, which focuses on strengthening of the paradigm of liberal education, encounters problems not only due to rapid changes in political, social, economic and cultural life but also because of the development of educational science itself. Therefore, it is particularly important to penetrate into the treasury of pedagogical thoughts of prominent educational researchers. B. Bitinas pedagogical thought embraces a big number of components of educational system analysed in the interdisciplinary context. A particular role is assigned to the philosophy of education, which facilitates linking of the essence of human existence with the spiritual dimension as unique power of the human nature that creates prerequisites for self-governance as well as for creation of authentic relations. Such a methodological approach opens up opportunities of theoretical substantiation of the process of education and its practical realisation. The contribution of Professor to determination of axiological fundamentals of education is of utmost significance: the essence of values, criteria, typology and hierarchy. In the background of the aforesaid questions, the principles of setting educational goals that focus on the authentic choice of holistic or hierarchical value system are highlighted. Therefore the value-based pluralism is identified as the main principle of development of axiological education content. The contribution of B. Bitinas to the deepening of the structure of the process of education is particularly relevant. The presented structure of educational situation allows to distinguish its components as well as to conduct a comprehensive analysis of the process of education in the specific situation. Educational science is incapable to implement the insight of B. Bitinas into the paradigm of synergetic, which serves as basis for methodology. This is a trend for future research, which is grounded on the Professor’s insights.